Use of Selective Serotonin Reuptake Inhibitors and Outcomes in Stroke Rehabilitation: A Prospective Observational Pilot Cohort Study - See-Hwee Yeo; Keng He Kong; Derek Chi-Kien Lim; Wai-Ping Yau (Adis, Springer Healthcare, 2019)
Abstract Purpose The aim of this study was to examine the association between selective serotonin reuptake inhibitor (SSRI) therapy and rehabilitation outcomes, specifically disability and quality of life (QOL), in a real-world setting of multi-ethnic Asian patients with first-ever stroke. Methods In this prospective observational pilot cohort study, we included patients with first-ever stroke admitted to two inpatient rehabilitation centres in Singapore between January and July 2018. Outcomes were measured using Functional Independence Measure (FIM)-motor scale, modified Barthel Index (MBI) and the Stroke and Aphasia Quality of Life Scale-39 generic (SAQOL-39g) questionnaire. Linear regression was used to assess the association between SSRI therapy and outcomes. Regression coefficients and 95% confidence intervals (CIs) were reported. Results Among 57 patients included for analyses, 38.6% received SSRIs. Although SSRI therapy was significantly associated with gains in MBI (coefficient 11.35; 95% CI 0.21-22.50) and SAQOL-39g overall score (coefficient 0.45; 95% CI 0.05-0.85) based on simple linear regression, no significant association between SSRI therapy and any of the investigated outcomes was found after adjustment for confounders. However, an increase in the mean number of physiotherapy and occupational therapy (PT/OT) sessions per day significantly improved FIM-motor (coefficient 16.86; 95% CI 2.64-31.07) and MBI (coefficient 22.79; 95% CI 2.35-43.23) scores. Conclusion SSRI therapy did not improve disability and QOL in multi-ethnic Asian patients with first-ever stroke undergoing rehabilitation.